Compressive behavior of thin-walled circular steel tubular columns filled with steel stirrup-reinforced compound concrete. (1st September 2018) - Wu, B.; Zhang, Q.; Chen, G.M.
Highlights: Demolished concrete lumps (DCLs) are used with fresh concrete in compound concrete. Effects of stirrups on compound concrete filled steel tubular column investigated. Strength and ductility can be increased by increasing steel tube thickness. Use of steel stirrups is more effective than increasing steel tube thickness. Distribution of stirrups has a significant effect on the effects of steel stirrups. Abstract: The reuse of coarsely crushed demolished concrete lumps (DCLs) with fresh concrete (FC) in compound concrete (i.e. concrete composed of DCLs and FC) provides a viable option to recycled concrete aggregates for recycling concrete waste. Compound concrete-filled steel tubular (CCFST) columns further improve the efficiency with which DCLs are used due to the advantages of concrete-filled steel tubular columns, such as improved strength and ductility. This paper presents an experimental study of the compressive behavior of thin-walled circular steel tubular columns filled with compound concrete with and without internal steel stirrups. Twenty CCFST columns were tested for experimental investigation of the effects of the replacement ratio of DCLs, the strength of the FC, the thickness of the steel tubes, and the distribution of steel stirrups. The test results show that steel stirrups can considerably enhance the load-carrying capacity of CCFST columns and significantly improve their ductility regardless of the strength of the FC, and a non-uniform layout (mainly in the middle height of the column) of steel stirrups can further enhance the performance of the CCFST columns without increasing the amount of steel. Based on the results, a simplified design method proposed for CCFST columns reinforced with internal steel stirrups compared well with the test results.